The Influence of Emotional Intelligence and Career Development on Employee Performance - Shinta Oktafien; Bachtiar Usman; Sarfilianty Anggiani (Jurnal Syntax Transformation, 2024)
This research is motivated by the low performance results shown by permanent lecturers at "B" Accredited Private Universities in Bandung City, especially in the field of research with the obligation for each lecturer to publish their scientific work in national or international journals. The aim of this research is to analyze the influence of Emotional Intelligence and Career Development on Employee Performance. This research is included in quantitative research which is used to test hypotheses with the results in the form of the significance of the relationship between the variables studied. The population of this study was all permanent lecturers at a "B" accredited private university in the city of Bandung, totaling 1009 people and with a sample size of 286 respondents. And the sampling technique used in this research is cluster sampling. Meanwhile, the data analysis used in this research is in the form of multiple regression analysis calculated using the SPSS 23.00 program. The research results show that Emotional Intelligence and Career Development, both partially and simultaneously, show a significant influence on Employee Performance.